i-Genius Learning Centre / Azrina Ahmad ... [et al.] - Ahmad, Azrina; Ahmad Mazlan, Ahmad Suffian; Md Isa @ Mansor, Mursyida; Hamsain, Mohd Yahya; Rasidi, Roslizawati; Rahmat, Nurul Aina (Faculty of Communication and Media Studies, 2003)
/-genius Learning Centre was established because we want to: 4 Introduce new learning method which is individualized and independent in our country. 4 Provide services to the students who live around the Bandar Utama. 4 Gain the business profit. 4 Increase the numbers of Bumiputera entrepreneurs in our country because as we notice, businesses are monopolized by the Chinese. 4 Compete with other competitors which more concentrate on teaching lesson without let the students use their IQ in answering the question given. 4 Educate the students with the simple skills of learning which more easy and fun.